Haploidentical Allogeneic Stem Cell Transplantation as a Superior Alternative for Patients With Mismatch Donors—A Single Center Experience in 152 Patients - Paul Jäger; Benno Biermann; Nora Liebers; Felicitas Schulz; Ben‐Niklas Baermann; Sören Twarock; Stefanie Geyh; Kathrin Nachtkamp; Patrick Tressin; Annika Kasprzak; Felix Matkey; Titus Watrin; et al. (eJHaem)
ABSTRACT Background Allogeneic hematopoietic stem cell transplantation (allo‐SCT) is a key treatment for hematologic malignancies, but donor selection impacts outcomes. Results In a cohort of 152 patients undergoing allo‐SCT from 2012 to 2023, haploidentical donors with post‐transplant cyclophosphamide (PTCy) showed superior survival compared to 9/10 mismatched unrelated donors (MMUD). Cox regression analysis revealed that patients not in complete remission (CR) before transplantation particularly benefited from haplo donors, while those with 9/10 MMUD and lacking CR had worse outcomes. Conclusion These results highlight the importance of donor selection, suggesting that haplo donors with PTCy may be preferable for patients not in CR, necessitating alternative approaches for others. Clinical trial registration The authors have confirmed clinical trial registration is not needed for this submission.